EKSISTENSIALISME MAHASISWA DI LINGKUNGAN PENDIDIKAN: MENENTUKAN MAKNA DIRI DI TENGAH TUNTUTAN AKADEMIK - Nurhayati; Nisa, Mazra; Thaahirah, Jihan; Purba, Ira Regina; Marito, Zaskia; Silalahi, Salwa Amaliansyah; Fadhilah, Wafiq Jiha (Yayasan Amanah Nur Aman, 2025)
This study explores the existential experiences of university students within the context of higher education, particularly how they perceive their own existence amid academic and social pressures. The aim of this research is to describe the existential realities faced by students through a descriptive qualitative approach, using reflective questionnaires and literature review. Data were collected from 38 student respondents from various universities in Indonesia. The findings reveal that most students experience identity crises, uncertainty about their life direction, and pressure from academic and family expectations. However, they also show awareness of their freedom to make decisions and a sense of responsibility for their life choices. The discussion connects the findings to existentialist thinkers such as Kierkegaard, Sartre, and Heidegger. The study examines four main aspects: crisis of meaning and personal struggle, freedom and life choices, existential reflection amid social-academic pressure, and freedom of thought along with personal responsibility. This study concludes that students are in the midst of an important existential process, where education should serve not only as a space for academic achievement, but also as a reflective journey to build authentic meaning and self-understanding. Therefore, a more humanistic and reflective educational approach is necessary to support students in discovering their true selves.